Research in times of crisis : research methods in the time of COVID-19 - Hill, Aaron D.; Lê, Jane K.; McKenny, Aaron F.; O'Kane, Paula; Paroutis, Sotirios; Smith, Anne D. (Research methodology in strategy and management, 2021)
Research Methodology in Strategy and Management advances understanding of the methods used to study organizations - including managers, strategies, and how firms succeed. Just like the impact felt across many other aspects of life and work, COVID-19 significantly changed the way we approach and conduct research. Many researchers will need to tread unfamiliar methodological ground to address these challenges and seize these opportunities to hone their craft, conducting interesting research in a novel environment. That is precisely why we are making 'crisis' the central focus of this volume. Research in Times of Crisis is an informative book for all academics and researchers working in the fields of management, strategy, international business, entrepreneurship and organization theory.